FACTORS AFFECTING TEACHERS’ TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (A SURVEY ON ECONOMICS TEACHER KNOWLEDGE) - Janah Sojanah; Suwatno Suwatno; Kodri Kodri; Amir Machmud (LPMPP Universitas Negeri Yogyakarta, 2021)
This study was conducted due to the lack of teachers’ Technological Pedagogical and Content Knowledge (TPACK). It examined the effects of teaching experience, training, facilities and infrastructure, self-efficacy, as well as motivation on teachers’ TPACK. The descriptive and explanatory methods with quantitative approaches were employed. The population of this study included 472 economics teachers in the Greater Bandung area, while the respondents were 217 economics teachers selected using the proportional probability sampling technique. The instrument used to collect the data was tried out to forty economics teachers. The instrument validity was measured using the CVR formula, and the instrument reliability was tested using construct reliability. The data were collected by means of questionnaires and then analyzed using descriptive analysis and Structural Equation Modeling (SEM). The results show that the teachers’ experience, training, facilities and infrastructure, self-efficacy, as well as motivation are at a low level. Likewise, the teachers’ TPACK seems to be low. Moreover, it is found that teaching experience, training, facilities and infrastructure, self-efficacy, as well as motivation have positive effects on teachers’ TPACK.